ORGANIZATION OF PHYSICAL EXERCISES FOR STUDENTS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Kholova Shakhnoza Mardonovna; Nomozboyeva Rukhshona (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article discusses the issues of effective organization of physical labor of children in preschool educational organizations. The importance of physical labor in ensuring the motor activity, safety and physical development of children is analyzed. Physical education, organization and upbringing of physical exercises, the role of educators and parents in this process is very important.